The Influence of Embodied Cognition Activities on Early Language Education Approaches for Small Preschoolers - Maria-Cristina Manea; Mușata-Dacia Bocoș (Babes-Bolyai University, 2024)
Embodied cognition activities involve active interactions that train the motor system, the perceptual system and physical interactions with the proximal environment. In the language education of young preschoolers, these types of activities train young preschoolers in the process of learning new words, their comprehension and correct pronunciation. The article presents the influence exerted by the "Integrated exploitation of sensory-motor stimuli" educational program with an emphasis on capitalizing on embodied cognition activities, in the early language education approaches of small preschoolers. Early language education through this type of activity proves effective because it encourages children to make connections between words and concepts using tactile, visual and motor experiences. This approach helps to develop strong connections between words and their meanings. The methods used were the observation of the language behavior of the preschooler and the psychopedagogical experiment method, and the applied research tools, the observation grid of the language behavior of the preschooler and the educational program "Integrated exploitation of sensory-motor stimuli". The study involved 98 small preschoolers, aged between 3 and 4 years, from 3 state preschool education units, from the urban and rural areas of Hunedoara County. The three educational units involved in the research are: "Mircea Sântimbreanu" Secondary School Brad, "Flore de Colț" Extended Program Kindergarten Brad and "Crișcior Extended Program Kindergarten".